Special education during the pandemic : considerations for change in practice - Obiakor, Festus E.; Banks, Tachelle; Rotatori, Anthony F. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"The COVID-19 pandemic has triggered many changes in K-12 education-some major, like learning remotely from home, and some minor, like sitting farther apart on the school bus. While most students have had routines interrupted, the children perhaps most affected by that disruption are special education students. The challenges we currently face should not undermine what we've accomplished over the last 60 years to protect students with disabilities and those for traditionally marginalized background. Instead, we must take an honest, proactive and collaborative approach to the challenges laid bare. To do so, we must reckon with the fact that during a pandemic that disproportionately impacted traditionally marginalized communities and people with disabilities, we collectively dropped the ball for students receiving special education services, and we need to consider the continued consequences. Further, we must acknowledge that many students with disabilities have found virtual and remote learning to be more liberating and accessible for their learning strengths, needs, and preferences. This text addresses how we reconcile these disparate realities of the special educational experience during pandemic. Students, parents, teachers, and school officials must align ourselves together so that we can provide the necessary services and support to students with disabilities during these unpredictable times and leverage opportunities to disrupt, improve and ignite educational experiences and opportunities for our children and youth, particularly students with disabilities"-- Provided by publisher.
Keywords: Special education -- Planning.; COVID-19 Pandemic, 2020-2023 -- Influence.; Special education -- Computer-assisted instruction.; Special education -- Parent participation.; Special education teachers -- In-service training.; Education -- Special Education -- General.; Teaching of students with different educational needs.; elektronické knihy; electronic books